Breast Cancer Research Protocols - Brooks, Susan A.; Harris, Adrian; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana Press, 2006)
Many new technologies involving large-scale analysis of gene expression, novel treatments, and emergent combined therapy approaches have opened fresh possibilities for understanding and effectively managing breast cancer. In Breast Cancer Research Protocols, active researchers and clinicians describe in detail both well-established and cutting-edge methods for investigating breast cancer biology not only in the laboratory, but also in clinical settings. These readily reproducible techniques solve a variety of problems, ranging from how to collect, store, and prepare human breast tumor samples for analysis, to analyzing cells in vivo and in vitro. Additional chapters address the technology of handling biopsies, new methods for analyzing genes and gene expression, markers of clinical outcome and progress, analysis of tumor-derived proteins and antigens, validating targets, and investigating the biology of newly discovered genes. The protocols follow the successful Methods in Molecular Medicine$1!" (Bseries format, each offering step-by-step laboratory instructions, an introduction outlining the principles behind the technique, lists of the necessary equipment and reagents, and tips on troubleshooting and avoiding known pitfalls. Comprehensive and highly practical, Breast Cancer Research Protocols offers laboratory and clinical researchers the tools needed to illuminate breast cancer biology and advance the efficacy of its treatment today.s
Preparation of Cell and Tissue Samples -- Breast Tissue Banking -- Frozen Biopsy Collection and Storage -- Serial Biopsies/Fine-Needle Aspirates and Their Assessment -- Breast Tissue Microarrays -- Preparation of Tumor Homogenates for Subsequent Preparation of Cytosols, Membrane Fractions, RNA, and DNA -- Isolation of RNA From Tumor Samples -- Isolation of DNA From Tumor Samples -- Laser-Assisted Microdissection and Isolation of DNA and RNA -- Markers of Clinical Outcome and Prognosis -- Traditional and Established Indicators of Prognosis and Treatment Success -- Sentinel Lymph Node Biopsy in Breast Cancer -- Pathological Evaluation of Axillary Sentinel Lymph Nodes in Breast Cancer -- Measurement of Estrogen Receptor Status by Immunocytochemistry in Paraffin Wax Sections -- Markers of Apoptosis -- Quantitative Angiogenesis in Breast Cancer -- Analysis of Tumor-Derived Proteins and Antigens -- Immunohistochemistry -- Detection of Aberrant Glycosylation in Breast Cancer Using Lectin Histochemistry -- SDS-PAGE and Western Blotting to Detect Proteins and Glycoproteins of Interest in Breast Cancer Research -- Breast Cancer Proteomics Using Two-Dimensional Electrophoresis -- Procedures for the Quantitative Protein Determination of Urokinase and Its Inhibitor, PAI-1, in Human Breast Cancer Tissue Extracts by ELISA -- Analysis of Genes and Gene Expression in Tumor Specimens -- Fluorescence In Situ Hybridization and Comparative Genomic Hybridization -- Fluorescence In Situ Hybridization Assessment of c-myc Gene Amplification in Breast Tumor Tissues -- Detection of HER2 Gene Amplification by Fluorescence In Situ Hybridization in Breast Cancer -- In Situ Hybridization Combined With Immunohistochemistry to Localize Gene Expression -- Quantitation of RNA by Ribonuclease Protection Assay -- Identification of Steroid Hormone-Regulated Genes in Breast Cancer -- Sequencing of the Tumor Suppressor Gene TP 53 -- Expression Profiling Using cDNA Microarrays -- Gene Expression Analysis Using Filter cDNA Microarrays -- Studying Cancer Cell Behavior in Vitro and In Vivo -- Methods to Analyze the Effects of the Urokinase System on Cancer Cell Adhesion, Proliferation, Migration, and Signal Transduction Events -- Phospho-Specific Antibodies as a Tool to Study In Vivo Regulation of BRCA1 After DNA Damage -- Models of Hormone Resistance In Vitro and In Vivo -- Generation of Genetically Modified Embryonic Stem Cells for the Development of Knockout Mouse Animal Model Systems -- In Vivo Xenograft Models of Breast Cancer Metastasis -- Neoadjuvant Endocrine Therapy Models -- Primary Mouse Endothelial Cell Culture for Assays of Angiogenesis.
Keywords: Medicine; Oncology; Medicine & Public Health; Oncology; Electronic books